A voz acena : a presença da voz na cena da aula - Azevedo, Alessandra Christina Arantes Abdala (2013)
The teacher´s voice, within the scenery of a class, reveals itself as a protagonist and it is used as a fundamental tool to develop the procedures that the teaching process requires. Under the expectation that something is reported, the teacher's voice marks its presence. The scenery: A school. The stage: The life-living classroom. A scenery where life makes and remakes all the time. Stage of fear, excitement, uncertainty, talking. Each and everyone is alert to the blackboard, arrested ears to the teacher‘s voice – which pulses, aspires, inspires, sings, shouts, creates echoes, emerges, flows, insinuates, speaks, sings, teaches! Inside this classroom scenery, the voice is in commandment. In it, there is an impression that the teacher speaks to his own ears, to hear his own voice, to his own-self, to imitate voice. He needs audience and not necessarily need for listeners. In this work, the regency of this scene was estranged and deterritorialized inside a philosophical discussion over the différance from Derrida‘s source. The linking between the voice and the listening occurred along this research by an intersection of the glottal method and the otobiographie gesture. As a part of the ―Escritoleituras‖ project: a way for reading and writing inside the living, OBEDUC/CAPES/INEP/UFMT were mobilized means to bring up, from ―Biografemas‖ workshops, a kind of intervention by which the results are empirical dimension perceived by teachers and regarding the presence of speech, resulting in a Phonodidaticário.